Reproductive performance of reindeer fed all-grain and hay-grain rations
Reproductive performance of grain-fed reindeer Rangifer tarandus) was evaluated over a 2-year period. Groups of pregnant reindeer were fed one of three rations, (1) 100% whole-grain barley, (2) 98.9% whole-grain barley and 1.2% mineral and trace element supplement, and (3) 70% whole-grain barley and 30% finely-chopped bluegrass hay. Reindeer fed unsupplemented whole-barley failed to produce a single live calf. The addition of mineral and trace element supplement to the ration did not result in any significant improvement in reproductive performance. Eighty-five percent of the reindeer consuming unsupplemented and supplemented all-barley rations became pregnant; however, 76% of the pregnancies resulted in stillborn calves. One-hundred percent of the cows maintained on the grain/hay ration produced live calves. We speculate that reproductive failure in reindeer cows maintained on all-grain rations is most likely a result of a diet induced disfunction in maternal rumen and/or carbohydrate metabolism rather than a micro-nutrient deficiency. More research is neeeded to determine which metabolic pathways are affected., number=2, journal=Rangifer, author=Blanchard, J. M. and Hauer, W. E., year=1986, month=Jun., pages=39–41